2012
DOI: 10.4081/ijas.2012.e63
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age of wild ideLeuciscus idus(L.) female on spawning effectiveness under controlled conditions

Abstract: The aim of this study was to determine the effect of age of female ide on spawning success under controlled conditions. All ide breeders were collected from one wild population. Data concerning reproductive parameters were collected during induced spawning under hatchery conditions. The age of mature females ranged from 4 (average weight 504 g) to 9 years (average weight 2540 g) and the youngest collected females (3+) (average weight 330 g) were immature. The females from group 4+ produced smaller oocytes (1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…However, if thermal anomalies occur just before spawning, a disturbance in the ovulation process may occur as well as a considerable deterioration of spawn quality, which manifests itself by low embryo survival rate and a high percentage of larvae deformation. A temperature decrease in such species as asp (Aspius aspius L.) or ide (Leuciscus idus L.) considerably delays ovulation (latency time) (Targońska et al, , 2012a. However, when the temperature increases beyond the set thermal optimum (maximum), one should expect a considerable decrease in the percentage of ovulation and the biological quality of oocytes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, if thermal anomalies occur just before spawning, a disturbance in the ovulation process may occur as well as a considerable deterioration of spawn quality, which manifests itself by low embryo survival rate and a high percentage of larvae deformation. A temperature decrease in such species as asp (Aspius aspius L.) or ide (Leuciscus idus L.) considerably delays ovulation (latency time) (Targońska et al, , 2012a. However, when the temperature increases beyond the set thermal optimum (maximum), one should expect a considerable decrease in the percentage of ovulation and the biological quality of oocytes.…”
Section: Discussionmentioning
confidence: 96%
“…In fish with one-off spawning, carp pituitary homogenate (CPH) is usually used in in-season reproduction, as well as preparations containing GnRH analogue with dopamine inhibitor (DA) or combinations of CPH with hCG (Kucharczyk et al, 2005;Brzuska, 2005Brzuska, , 2006Kristan et al, 2013;Nowosad et al, 2014b). In batch-spawning fish, like in percids (such as perch Perca fluviatilis L.), there can be other agents used successfully except for the preparations mentioned above, such as hCG, FSH+LH, or analogues of GnRH (Kucharczyk et al, 1998;Targońska and Kucharczyk, 2011;Targońska et al, 2012a). Therefore, even those preparations which do not work, or which work only to a limited extent with cyprinid fish with one spawn in the season, can be used to induce final gamete maturation in fish which spawn in portions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the age of fish can influence the quality of gametes (Quintero et al, 2011;Targonska et al, 2012;Aliniya et al, 2013). Thus, to obtain good-quality offspring, the age of the breeders must be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…spawning just after ice break up or even earlier and returning immediately to the sea) and sea-life further away from the coast where fishing pressure is lower. However, older ide may produce eggs with lower biological quality or not reproduce at all (Targońska et al, 2012) and therefore may have limited positive influence on spawning stock viability, especially when they dominate (e.g. Saunja and Matsalu Bay).…”
Section: Discussionmentioning
confidence: 98%
“…The only peer-reviewed study on ide age used scales and was conducted with female fish that originated from a Polish freshwater lake (Targońska et al, 2012). Unfortunately, the growth rate was not in the scope of their study as only pre-spawn total weights of fish were provided.…”
Section: Introductionmentioning
confidence: 99%